1994
DOI: 10.3406/psy.1994.28751
|View full text |Cite
|
Sign up to set email alerts
|

Émergence d'une unité sublexicale au cours d'une tâche d'abréviation

Abstract: Summary: Emergence of sublexical unit during an abbreviation task. Are there one or more linguistic units which play a basic role in accessing the mental lexicon? To answer this question we have studied a common process: the abbreviation process, which is composed of two stages: 1) abbreviation production (time and space gains) and 2) reconstruction of the source word from the abbreviation. The existence of this second stage, which requires access to the mental lexicon, has led us to think that abbreviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Establishing the optimal sublexical fragment for such activation would provide information about the structure of the lexical representation of polysyllabic words. Because Rouibah and Tiberghien (1994) observed that participants preferentially abbreviated French words by their BOSS and because an abbreviation is a word fragment from which the whole word is supposed to be retrieved, one can make the prediction that the BOSS will be preferred over the syllable as the activation unit. If this is the case, it means that the sublexical unit implicated in French visual word recognition is different from the one implicated in French spoken word recognition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing the optimal sublexical fragment for such activation would provide information about the structure of the lexical representation of polysyllabic words. Because Rouibah and Tiberghien (1994) observed that participants preferentially abbreviated French words by their BOSS and because an abbreviation is a word fragment from which the whole word is supposed to be retrieved, one can make the prediction that the BOSS will be preferred over the syllable as the activation unit. If this is the case, it means that the sublexical unit implicated in French visual word recognition is different from the one implicated in French spoken word recognition.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, a study carried out by Rouibah and Tiberghien (1994) gave some indication that the BOSS plays a role in the processing of written French. Rouibah and Tiberghien observed that when participants had to freely abbreviate spoken French disyllabic words, they preferentially produced abbreviations of the BOSS type (70% of the total production), whatever the structure of the syllable boundary was (e.g., one consonant at the syllable boundary, as in SOLEIL; two consonants at the syllable boundary, with one being the first syllable coda and one being the second syllable onset, as in COMBAT; or two consonants at the syllable boundary, forming the second syllable onset, as in LIVRET).…”
Section: Visual Processing Of Syllabic Structure In Frenchmentioning
confidence: 99%